Comparison of the effects of 10 GLP-1 RA and SGLT2 inhibitor interventions on cardiovascular, mortality, and kidney outcomes in type 2 diabetes: A network meta-analysis of large randomized trials - Wei, Xu-Bin (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• The relative benefit of new antidiabetic drugs for cardiorenal endpoints is unclear. • The most efficacious drugs vary with different cardiorenal endpoints. • Subcutaneous semaglutide and albiglutide are most effective for cardiac events. • Canagliflozin and empagliflozin are most effective for heart failure hospitalization. • Dapagliflozin and empagliflozin are most effective for kidney function progression.